Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kinerja Keuangan Pada 19 Kabupaten dan Kota di Sumatera Barat - Joni Fernandes; Annisa Nur Hilwani (Jurnal Ilmiah Pendidikan Scholastic, 2021)
The purpose of this research was to examine the effect of local revenue and balance funds on financial performance. The sample in this study used a census method in which the entire population would be used as a sample, so the sample in this study was the Municipal Government in West Sumatra, consisting of 7 cities and 12 regencies. The type of data in this study is the ratio. The data collection technique in this research is documentation technique. The application used to process data in the study is Eviews. The results show that local revenue has a positive effect on financial performance and the Balanced Fund has a negative effect on financial performance, this statement is evidenced by the results of the t test with a significance level of less than 0,05.